Symbiont footprints highlight the diversity of scleractinian‐associated Zanclea hydrozoans (Cnidaria, Hydrozoa). (18th March 2019) - Manca, Federica; Puce, Stefania; Caragnano, Annalisa; Maggioni, Davide; Pica, Daniela; Seveso, Davide; Galli, Paolo; Montano, Simone
Abstract: Hydrozoans of the genus Zanclea have been acknowledged only recently as a fundamental component of the highly diverse fauna associated with reef‐building scleractinian corals. Although widely distributed in coral reefs and demonstrated to be important in protecting corals from predation and diseases, the biodiversity of these hydrozoans remains enigmatic due to the paucity of available morphological characters, incomplete morphological characterisations and the possible existence of cryptic species. Recently, molecular techniques have revealed the existence of multiple hidden genetic lineages not yet supported by diagnostic morphological characters. In this work, we further explore the morpho‐diversity of three genetic lineages, namely Zanclea associated with the coral genera Goniastrea (clade I), Porites (clade II) and Pavona (clade VI). Aside from providing a complete classical characterisation of the polyp and medusa stage of each clade, we searched for new potential taxonomic indicators either on symbiotic hydroids or on host corals. On the hydroids, statistical analyses on almost 7, 000 nematocyst capsules revealed a significant difference in terms of nematocyst size among the three Zanclea clades investigated. On each host coral genus, we identified peculiar skeletal modifications related to the presence of Zanclea symbionts. Lastly, we discussed the potential diagnostic value of these footprints in the characterisation of Zanclea –scleractinian associations.